Importancia del tratamiento integral precoz y regular en niños con malformación congénita de labio y/o paladar hendido - Osorio, María Cecilia; Mejía, Carlos; Argote , Olga Patricia; Osorio, Isabel Cristina; Viteri, Alcira (Revista Estomatología, 1993)
It is presented an article of an exploratory, descriptive an correlated study in a population of patients with palate andJ or lip fisures, with no ectodermic syndromes. It is analyzed their neurovegetative, respiratory and phonologic functions, the otological and auditive state, speech articulation, as well as their facial estomathological and phono articulator characteristi cs. It is concluded that the ideal treatment for these entities, specially for their complexity, is the integral, precocious and regular, on time, attention. Preventingand correcting~ inadecuate conducts that produce notorius defects and abnormal development of speech, with the consequent social reject. Statistical tables are given to mnfirm the conclusions.